Evaluasi Induksi Umbi Mikro secara In Vitro pada Beberapa Kultivar Bawang Merah (Allium cepa L. kelompok Aggregatum) pada Kondisi Sukrosa Tinggi - Nofiya Ruswanti; Widhi Dyah Sawitri; Muhammad Idris; Valentina Dwi Suci Handayani; Ani Widiastuti (Vegetalika, 2026)
Development of microbulb in shallots (Allium cepa L. Aggregatum group) is induced by adding a higher sucrose content to the in vitro culture medium. Therefore, this study was conducted to evaluate microbulb formation by enhancing the sucrose concentration up to 8%. The ‘Sanren’ cultivar was used as a model to observe the effect of additional sucrose treatment, between 3% (P1) and 8% (P2), in Murashige and Skoog (MS0) media over ten weeks. The result showed that microbulbs in the ‘Sanren’ cultivar developed successfully in the P2 treatment. Following these findings, several other shallot cultivars— ‘Lokananta’, ‘Maserati’, and ‘Merdeka’—were assessed using the 8% sucrose concentration to trigger microbulb formation. The microbulbs initially formed following a color change at the plant’s basal part eight weeks after planting. Difference in response regarding plant height and microbulb weight were observed among the cultivars. Plant height was greater in the ‘Sanren’ than in ‘Lokananta’ and ‘Maserati’ at eight weeks after planting. At ten weeks after planting, ‘Maserati’ and ‘Merdeka’ exhibited the highest microbulb weight. In this study, we assumed that each cultivar has a differing ability to absorb the carbon source, which in turn affects the development of microbulb formation in the in vitro medium. The higher sucrose content in the in vitro medium mimics the condition where photosynthates are translocated to the basal plant, leading to shallot microbulb formation. This innovation has the potential to facilitate efficient in vitro microbulb production through the addition of 8% sucrose.